Significant Succession of Intestinal Bacterial Community and Function During the Initial 72 Hours of Acute Pancreatitis in Rats - Liu, Jinbo; Luo, Ming; Qin, Shu; Li, Bo; Huang, Lin; Xia, Xianming (Frontiers in Cellular and Infection Microbiology, 2022)
Acute pancreatitis (AP) is followed by structural and functional changes in the intestine, resulting from microbiome dysbiosis. However, it remains unclear how gut microbiome changes within the initial 72h of onset. In this study, severe acute pancreatitis (SAP), mild acute pancreatitis (MAP), and sham operation (SO) were replicated in rat models. 16S ribosomal RNA gene sequencing were used to explore the gut bacteria community. The predicted Cluster of Orthologous Genes (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathways were associated with the 16S rRNA profiles. Compared to the SO group, significant community succession was found during the initial 72h in AP group. At 72 h after AP induction, the Firmicutes/Bacteroidetes (F/B) ratios were significantly different, with the highest ratio in SAP group and the lowest in MAP group. Lactobacillus was the most abundant genus, but it nearly disappeared in SAP rats at 72 h. Clostridiaceae 1 and Clostridium sensu stricto 1 were significantly enriched in AP group. Bacteroidales S24-7 and Bacteroidales S24-7 group norank were enriched in MAP group, while Collinsella, Morganella, and Blautia were enriched in SAP group. Lactobacillus was significantly correlated with nine COGs. Nine COGs showed significant differences between AP group and SO group. Moreover, four COGs showed significant differences between the MAP and SAP groups. KEGG Level_3 pathways propanoate metabolism (Ko00640) in AP group was significantly higher than that in SO group. The aspartate‒ammonia ligase and four KEGG orthology terms of the AP group were lower than that in the SO group, respectively. All these results suggest that the intestinal bacterial community structure and function was changed during the initial 72h in AP rats. The intestinal F/B ratio and the relative abundance of Lactobacillus could be potential markers for early diagnosis of MAP and SAP. The genus Clostridium sensu stricto 1 was the most enriched genus in AP, and may be an important marker for AP.